Eletrocerâmicas de BNBK dopadas com tântalo: processamento, fenomenologia e propriedades de armazenamento de energia - Barbosa Quiroga, David Antonio (2019)
Global energy demand for high energy storage capability materials associated with the search for lead-free electroceramic materials with suitable properties for applications has become the major topic in functional materials research. In this context, bismuth sodium titanate (Bi0,5Na0,5TiO3, BNT) ceramics have attracted great attention by mimicking some characteristics of dominant material in applications, lead zirconate titanate (PbZr1-xTixO3, PZT).Starting from two compositions belonging to morphotropic phase boundary (MPB) of the ternary system xBi0,5Na0,5TiO3 - 0, 72(1 - x)Bi0,5K0,5TiO3 - 0, 28(1 - x)BaTiO3 (BNBK100x, x = 0, 86 e 0, 88), the Ta-doped (0.01, 0.015 and 0.02 mol) ceramics processing conditions have been optimized and the influence of this cation on the structural, morphological, electric, mechanical and energy storage properties of Ta-doped ceramics was evaluated. From the structural viewpoint, the stabilization and coexistence of the tetragonal phases with different symmetries was obtained with Ta doping. The BNBK86Ta100α and BNBK88Ta100α ceramics morphology were affected by the Ta doping, being the average grain size decreased with increasing of the Ta content. In the comparative analysis of the dielectric and mechanical responses were identified the temperatures of three anomalies and phenomenologically described as: Td, related with the ferroelectric long-range ordering loss and the tetragonal to pseudocubic phase transition beginning; TRE associated with the paraelectric transition and Tm related to the maximum value of the real part of dielectric permittivity, where Td < TRE < Tm. A strong dependence of the height of Tm anomaly with Ta content was observed, being the Tm peak height reduced with the Ta increasing. From charge compensation mechanisms which occur with the Ta5+ ion substitution in BNBK ceramics, we conclude that the Ta doping reduces the oxygen vacancies concentration, give rise to experimental evidence which that Tm anomaly should be related with the interfacial polarization created by oxygen vacancies mobility. The ferroelectric properties of the Ta-doped ceramics showed that the Ta doping reduces the long-range ferroelectric ordering, resulting in the relaxor state stabilization at lower temperatures when compared with the pure BNBK system. On the other hand, the results of the energy storage densities showed an efficiency enhancement as a function of Ta content, resulting in exceptional values of the order of 90% with good thermal stability at high temperatures.